Meningkatkan Mutu Pendidikan Santri dengan Adanya Bimbingan Belajar di Masa Pandemi di Pondok Pesantren Mahir Arriyadl Ringinagung Keling Kepung Kediri - Sutantri Sutantri; Ellyda Retpitasari; Muhammad Ahsanun Ni’am (PROSIDING SEMINAR NASIONAL PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2022)
With the uncontrolled increase in Covid-19 cases, the Government has decided to take the policy of Enforcement of Community Activity Restrictions (PPKM) in the entire Java-Bali region from the village to the provincial level in dealing with the Corona virus or Covid-19 pandemic in the country. The policy was taken after the government assessed this disease as a disease with high risk factors. The current war against Covid19 requires people to be active at home, keep their distance from other people and avoid crowds. Conditions like this force a solution caused by the impact of Covid-19 which has an impact on several existing aspects, one of which is in the field of education. Which can affect the decline in the quality of existing education, by using the PAR (Participatory Action Research) research approach which is one of the research models that is looking for something to link the research process into the process of social change, solutions can be offered to improve the quality of education. with the holding of tutoring. So that in tackling the decline in the quality of education that exists during the current pandemic, it is considered very appropriate and correct.